Substituição do milho pelo produto do processamento do caju para bovinos de corte em pastejo - Souza, Hozane Alves de (2019)
The purpose of this study was to evaluate the effect of maize replacement by the product of the dehydrated cashew processing (PCD) in the supplements on intake, digestibility and nitrogen (N) metabolism in grazing beef cattle. Five Nellore bulls with an average body weight of 359 ± 34.8 kg, whice were used in a 5 × 5 latin square design. The animals were kept in five Marandu grass (Urochloa brizantha cv. Marandu) paddocks of 0.32 ha each. Five protein-energy isonitrogenated supplements (310 g of crude protein (CP)/ kg on supplement of fresh matter) with different levels of replacement of maize by PCD (0, 0.25, 0.50, 0.75 or 1.00 g/g on fresh basis) supplied in the among of 1.0 kg/animal/day. The replacement of maize by PCD linearly reduced of supplement DM (P = 0.0741), total DM (P = 0.0744), CP (P = 0.0398) and digestible organic matter (P = 0.0142) but did not affect the pasture DM (P = 0.2253) intakes. However, linearly increased of indigestible neutral detergent insoluble fiber (P = 0.0734) and total tannins (P < 0.0001) intakes. The replacement of maize by PCD linearly reduced the total digestibility coefficients of DM (P = 0.0051), organic matter (P = 0.0033), CP (P = 0.0579), neutral detergent insoluble fiber (P = 0.0744), and dietary digestible organic matter (P = 0.0035). The replacement of maize by PCD linearly reduced N retention (P = 0.0808), synthesis of microbial N (P = 0.0222), ruminal ammoniacal N (P = 0.0533) and serum N ureic (P = 0.0265), but did not affect the fecal (P = 0.5865) and urinary (P = 0.2249) excretions of N and the utilization of N (P = 0.3358) and microbial (P = 0.3277) efficiencies. It is concluded that the replacement of maize by processing cashew product of the the intake, total digestibility coefficients, microbial nitrogen synthesis and nitrogen retention reduces.